2002
DOI: 10.1159/000063096
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Feeding in Prevention of Urinary Tract Infection, Bacterial Sepsis and Necrotizing Enterocolitis in Preterm Infants

Abstract: Background: It has been suggested that probiotics can reduce the overgrowth of pathogens in the bowels of preterm infants and contribute to the reduction of the incidence of nosocomial infections in neonatal intensive care units (NICUs). The purpose of this study was to evaluate the effectiveness of Lactobacillus GG supplementation in reducing the incidence of urinary tract infections (UTIs), bacterial sepsis and necrotizing enterocolitis (NEC) in preterm infants. Methods: A double-blind study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
259
4
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(285 citation statements)
references
References 36 publications
7
259
4
14
Order By: Relevance
“…In addition, questions regarding the safety and efficacy of delivering probiotic bacteria to pre-term infants have not been fully answered, since not all studies have shown beneficial effects of probiotics. In a study by Dani et al [21], infants treated with Lactobacillus were shown to have an increased incidence of sepsis, and the observed decrease in NEC incidence was not statistically significant. Similarly, Land et al [22] observed cases of Lactobacillus sepsis in infants treated with probiotics.…”
Section: Possible Treatment For Necmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, questions regarding the safety and efficacy of delivering probiotic bacteria to pre-term infants have not been fully answered, since not all studies have shown beneficial effects of probiotics. In a study by Dani et al [21], infants treated with Lactobacillus were shown to have an increased incidence of sepsis, and the observed decrease in NEC incidence was not statistically significant. Similarly, Land et al [22] observed cases of Lactobacillus sepsis in infants treated with probiotics.…”
Section: Possible Treatment For Necmentioning
confidence: 94%
“…However, point E lies in the region where the model predicts that probiotic treatment can actually be harmful, lowering the level of B L (0) needed to induce disease, for a certain range of k. For this parameter set, probiotics contribute to threshold crossing in the model, enhancing the immune response and further increasing permeability in a way that is not resolved by subsequent decreases in luminal bacterial levels. The existence of such a region may help explain clinical studies in which probiotics did not reduce the incidence of NEC and in fact led to bacterial sepsis [21,22]. Figure 6D provides a summary of predicted health and disease regions in the (k,r 1 ) plane.…”
Section: Model Predictions In the Presence Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These infants may be less likely to develop NEC (51)(52)(53), and while concern has long existed about probiotic strain-associated sepsis, this risk has not been born out in larger trials. However, studies overall have had mixed results (54,55). Infants do not develop IBS, and develop IBD only in extremely rare cases, but the apparent safety of probiotics in this group is reassuring that the risk for vulnerable or immunocompromised patients may be relatively low.…”
Section: Ibdmentioning
confidence: 99%
“…In 1999, Hoyos and colleagues reported the outcome of a cohort study, in which, probiotic administration was associated with a reduction in the incidence of necrotizing enterocolitis [53]. Between 2003 and 2006, several randomised studies reported a reduction in the incidence of NEC among preterm babies recruited to probiotic trials (and receiving the probiotic intervention) though not all these studies were designed to evaluate NEC as a primary outcome [54][55][56][57][58][59]. The first meta-analysis combining these results was published in 2007 and concluded that probiotics might reduce the risk of NEC in preterm babies born less 33 weeks gestation [60].…”
Section: Probiotics For the Prevention Of Necmentioning
confidence: 99%